(untitled) (Prilozi za orijentalnu filologiju, 2017)
The damage done to the cultural and historical heritage, can certainly be added to the overall picture of suffering and tribulation caused by aggression to Bosnia and Herzegovina 1992-1995. Shelling and mining of numerous places of worship, mosques, churches and monasteries, libraries, clock-towers and public facilities and housing fund, the aggressor was destroying the nucleus of religious and national life of the population. Only in Banja Luka, betvveen September, 9th and December 15th, 1993, 15 mosques, 6 mausoleums, 5 fountains, large number of graveyards and clock-towers. However, destruction of Islamic places of worship started even earlier. It is well known that Banja Luka became the Capital of Bosnian sanjak mid 16* century, and in 1580 the Capital of Bosnian eyalet, what guaranteed a faster urban development. From 16* to 19* century 45 mosques were built in Banja Luka together with as many accompanying settlement (mahala) and four marketplaces (čaršija) on the banks of Vrbas river. Especially beautiful were Ferhadija mosque (built in 1579) and Amaudija (in 1595). Destruction of the Islamic religious facilities started immediately after the defeat of the Ottoman armada in Vienna (1683) and peace signed in Karlovac (1699), and continued in 1737, when, during the reign of emperor Charles the Sixth, Banja Luka was under siege by Prince Hildburghausen. Preparation of this battle (July 24* to August 4*) and attacks by Hildburghausen’s troops, arrangement of artillery, as well as pontoon bridges, will include đrawing many maps and plans by the engineers of Austrian army. That is how a large number of the oldest maps and dravvings of Banja Luka were produced. Besides the fact that those were the oldest documents on Banja Luka of the kind, these maps are important proofs of urban development of early Banja Luka, especially the mosques that were exposed to destruction in the mentioned battle. This destruction lead to changes in architectural design of these facilities. Studying of history of the city of Banja Luka according to these documents is very complex and requires correct interpretation of everything that these documents contain, having in mind the environment they were produced in and their original purpose.